Unexpected Foreign Body-Induced Small Bowel adenocarcinoma: A Case Report - Zhang Y; Li HH; Ye MF; Li WW; Zhang C; Wang HF (Dove Medical Press, 2024)
Yu Zhang,1 Hong-Hai Li,1 Min-Feng Ye,1 Wei-Wei Li,2 Chu Zhang,3 Hai-Feng Wang1 1Department of Gastrointestinal Surgery, Shaoxing People's Hospital, Shaoxing, Zhejiang Province, 312000, People's Republic of China; 2Department of Gastroenterology, Shaoxing People's Hospital, Shaoxing, Zhejiang Province, 312000, People's Republic of China; 3Department of Thoracic Surgery, Shaoxing People's Hospital, Shaoxing, Zhejiang Province, 312000, People's Republic of ChinaCorrespondence: Hai-Feng Wang, Department of Gastrointestinal Surgery, Shaoxing People's Hospital, No. 568 Zhongxing North Road, Shaoxing, Zhejiang Province, 312000, People's Republic of China, Email drwanghaifeng01@163.comBackground: Foreign body-induced cancer is a traditional way of understanding cancer development. The induction of cancers by exogenous foreign bodies has been identified in many organs. However, small bowel adenocarcinoma induced by foreign bodies has not been reported in the literature, although the incidence of small bowel adenocarcinoma is increasing globally.Case Presentation: A 70-year-old man was hospitalized for persistent right-sided abdominal pain for 3 months. Abdominal computed tomography revealed localized thickening and clustering of the small bowel wall in the right abdominal cavity. A comminuted fracture of the right 11th rib protruding into the abdominal cavity was observed, with a bone fragment located within the intestinal mass. Exploratory laparotomy was performed, and extensive adhesions were noted among the greater omentum, small bowel, mesentery, and right abdominal wall. Radical resection and lymph node dissection of the affected small bowel and appendix were performed. We also excised the rib end and repaired the abdominal wall to prevent further irritation. The patient was discharged 12 days post-surgery and follow-up assessments revealed no reported discomfort.Conclusion: We first report a case of small bowel adenocarcinoma induced by self-bone tissue, along with successful radical tumor excision and thorough foreign body removal. This case highlights the significant role of chronic inflammation in carcinogenesis.Keywords: foreign body, small bowel adenocarcinoma, chronic inflammation, rib fracture, case report